Plastic Deformation by Grain Boundary Motion: Experiments and Simulations - Molodov, Dmitri A; Mishin, Yuri (Microstructural Design of Advanced Engineering Materials, 2013)
This chapter presents an overview of stress‐driven grain boundary (GB) motion coupled to shear deformation, focusing, and its role in plastic deformation of polycrystalline materials. We review the phenomenology, the coupled GB motion, and the simulation and experimental methodologies employed in its studies. The current status and the most active research directions in this field are discussed, including the geometric theory of coupling, the multiplicity of coupling modes and its relation to crystal symmetry, the dynamics of coupled GB migration and its atomic mechanisms, the coupled motion of asymmetric and more general types of GBs, and the connection between the coupling effect and grain rotation. Throughout this discussion, we highlight the critical role of the interaction between experiments, theory, and simulations that enabled the recent progress in understanding this important phenomenon. We conclude by outlining the unresolved problems and anticipated future developments in this field.